Multifunctional cyber‐physical system testbed based on a source‐grid combined scheduling control simulation system. Issue 12 (27th February 2017) - Zhang, Haibo; Ge, Dandan; Liu, Jizhen; Zhang, Yi
Abstract : To establish a real closed‐loop control centre testing environment for a cyber–physical power system, a cyber–physical testbed was established by integrating industry supervisory control and data acquisition with a source‐grid co‐simulation system in the laboratory at the North China Electric Power University. The testbed employs a multi‐time scale interface and virtual remote terminal units to overcome the shortcomings of the real‐time digital simulator. Physical simulation was performed with a source‐grid co‐simulation system based on a real‐time digital simulator. Control system simulation was implemented using a commercial energy management system. The testbed was also integrated with a wide‐area‐network emulator to provide wide‐area‐network emulation and advanced attack simulation. An overview of the system and the key technologies used in the cyber–physical system testbed is provided in this study. In addition, two specific cyberattacks are simulated to demonstrate the capacity of the cyber–physical system testbed.